2002
DOI: 10.1210/jcem.87.2.8200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Adipocyte Gene Expression by Thyroid Hormone

Abstract: Thyroid hormones are key regulators of metabolism. In adipose tissue, changes in thyroid status result in alterations of lipolytic capacity. The effects of these hormones are mediated by thyroid hormone receptors that modulate gene transcription. Very few target genes have been identified in adipose tissue. To investigate the effect of T(3) on gene expression in human adipocytes, primary cultures of human sc adipose tissue explants were treated with T(3). (32)P-labeled cDNA probes prepared from isolated adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 32 publications
3
63
0
9
Order By: Relevance
“…7, C and D). These data are consistent with recent studies using human primary adipocyte culture (42). These results indicated that impaired lipolysis in P398H mice was not due to reduced expression of ␤-adrenergic receptors.…”
Section: Generation Of P398h Mutantsupporting
confidence: 93%
“…7, C and D). These data are consistent with recent studies using human primary adipocyte culture (42). These results indicated that impaired lipolysis in P398H mice was not due to reduced expression of ␤-adrenergic receptors.…”
Section: Generation Of P398h Mutantsupporting
confidence: 93%
“…Previous work has clearly established the importance of transcriptional activation by nuclear receptors in both the control of adipogenesis and the regulation of energy balance by thermogenesis, with PPARs playing a central role (4)(5)(6)(7)(8)(9)(10)(11)(12). Spiegelman and coworkers (22,23,24) have provided substantial evidence to indicate that PGC-1␣ is a key transcriptional coactivator and metabolic regulator in BAT, muscle, and liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, energy is dissipated by generating heat in brown adipose tissue (BAT) and skeletal muscles by regulating the uncoupling of ATP production from respiration. Many of these metabolic processes are controlled in part by nuclear receptors (4,5), including peroxisome proliferatoractivated receptors (PPARs) (6,7), thyroid hormone receptor (8,9), estrogen receptor ␣ (ER␣) (10,11), and ER-related receptor ␣ (ERR␣) (12). The best characterized of these are the PPARs, with PPAR␥ and PPAR␣ playing an essential role in adipogenesis (13)(14)(15)(16) and in thermogenesis and fatty acid oxidation (17)(18)(19), respectively, whereas recent studies have implicated a role for PPAR␦ in lipid homeostasis (20).…”
mentioning
confidence: 99%
“…The specimens of subcutaneous fat were digested using collagenase (type 1; Biochrom, Berlin, Germany) as described previously [23]. Mature adipocytes and the stroma vascular fraction (SVF) were separated by centrifugation, lysed with denaturing buffer from the RNeasy total RNA Mini Kit (Qiagen), and then stored at −80°C prior to mRNA preparation.…”
Section: Clinical Investigation Protocolsmentioning
confidence: 99%